Inefficiency of the penal system in increasing crime - Gómez Pilco, Elke Lizeth Génesis (2020)
When media criminal populism sticks to cajole the population with increased penalties to curb the crime rate in crime matters, we see that its efforts are ineffective given that its measures, in addition to being demagogic, are short-term, ephemeral without any type of technical, sociological diagnosis, among other pertinent edges. That is why this work focuses on analyzing and proposing that the criminal system has succumbed to the abyss by the competent bodies, who do not strengthen their academic-scientific bastion have been overwhelmed by the political and economic class before those who cannot provide serious, profound and effective alternatives to stop the fight against crime.